2019
DOI: 10.3389/fendo.2019.00337
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Genetics of Fractures in Osteoporosis

Abstract: Genetic susceptibility, together with old age, female sex, and low bone mineral density (BMD) are amongst the strongest determinants of fracture risk. Tmost recent large-scale genome-wide association study (GWAS) meta-analysis has yielded fifteen loci. This review focuses on the advances in the research of genetic determinants of fracture risk. We first discuss the genetic architecture of fracture risk, touching upon different methods and overall findings. We then discuss in a second paragraph the most recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 103 publications
0
33
0
Order By: Relevance
“…Early reports have indicated that hereditary factors may play a role in PLO. Osteoporotic fractures at younger age more often have a genetic cause (68,69), in contrast to osteoporotic fractures at older ages which are often due to simple postmenopausal osteoporosis. Remarkably, a high prevalence of fractures has been reported in cases of mothers with PLO (70).…”
Section: Geneticsmentioning
confidence: 99%
“…Early reports have indicated that hereditary factors may play a role in PLO. Osteoporotic fractures at younger age more often have a genetic cause (68,69), in contrast to osteoporotic fractures at older ages which are often due to simple postmenopausal osteoporosis. Remarkably, a high prevalence of fractures has been reported in cases of mothers with PLO (70).…”
Section: Geneticsmentioning
confidence: 99%
“…With more fracture-related genetic components being discovered, a more significant effect of PGS on fracture risk prediction should be foreseen. Another possible reason for the minor effect of PGS on fracture outcomes observed in the present study is that, similar to other age-related traits, the heritability of fracture risk decreases with age [32]. Since the analytic sample consisted of older women, the effect mediated through genetic influences on bone turnover, and bone geometry or non-skeletal factors such as cognitive function, neuromuscular control, visual acuity, or other factors related to the risk of falling might be more attributable to the predisposition of fracture [33].…”
Section: Discussionmentioning
confidence: 62%
“…However, in the multivariate analysis, genetic profiling was demonstrated not to be a significant predictor of MOF and any fracture, after T-score classification was adjusted for. Prior twin studies demonstrated that the heritable component of fracture is largely independent of BMD [30,31], whereas the reported fracture-related genetic variants are also associated with BMD [32]. Due to the study power issue, GWAS for dichotomous disease as a direct outcome has yielded relatively lower numbers of loci discovered, and this is also the concern for osteoporotic fracture studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS have revolutionized the field of genetics of complex traits and common diseases, where osteoporosis is no exception. There are several reviews describing in detail the findings arising from the Genetic Factors of Osteoporosis (GEFOS) consortium, and the UK Biobank ( 56 58 ). Currently, there are close to thousands of variants associated with increased risk of osteoporosis ( 12 , 59 62 ).…”
Section: What Have We Learned From Complex Skeletal Traits?mentioning
confidence: 99%